Analysis of conical liquid antenna for wide range of frequencies. (19th November 2021) - Roopa, S.; Kumar, E. Kiran
A novel flexible conical liquid antenna fed by a probe pin is proposed in this paper. The proposed antenna is tested with three types of liquids like pure water, glycerin, and sea water and is analysed to achieve a voltage standing wave ratio of 1 to 2 over frequency range of 300-850 MHz. The simulation and experimental results validate that a compact, cost effective proposed conical antenna achieves wide range of frequencies with low radar cross section and omni directional radiation pattern. For a conical liquid antenna, the gain achieved by the experimental results is 2 dBi which is approximated to the gain achieved from simulation results that is around 1.89 dBi. Also, antenna measurements like radiation pattern, gain, voltage standing wave ratio and bandwidth of different liquids are compared using vector network analyser.